GE_GERICHTE C/9670/2014 vom 6. März 2015 - GE Cour de justice (2015)
MESURE PROVISIONNELLE; PROTECTION DE LA PERSONNALITÉ; AUDITION DE L'ENFANT | CPC.254.1; CDE.12; CC.28; CC.28b.1; CPC.261; CPC.343.1.a; CPC.343.3